Regulators of pluripotency and their implications in regenerative medicine - El-Badawy A (Dove Medical Press, 2015)
Ahmed El-Badawy, Nagwa El-Badri Center of Excellence for Stem Cells and Regenerative Medicine, Zewail City of Science and Technology, Giza, Egypt Abstract: The ultimate goal of regenerative medicine is to replace damaged tissues with new functioning ones. This can potentially be accomplished by stem cell transplantation. While stem cell transplantation for blood diseases has been increasingly successful, widespread application of stem cell therapy in the clinic has shown limited results. Despite successful efforts to refine existing methodologies and to develop better ones for reprogramming, clinical application of stem cell therapy suffers from issues related to the safety of the transplanted cells, as well as the low efficiency of reprogramming technology. Better understanding of the underlying mechanism(s) involved in pluripotency should accelerate the clinical application of stem cell transplantation for regenerative purposes. This review outlines the main decision-making factors involved in pluripotency, focusing on the role of microRNAs, epigenetic modification, signaling pathways, and toll-like receptors. Of special interest is the role of toll-like receptors in pluripotency, where emerging data indicate that the innate immune system plays a vital role in reprogramming. Based on these data, we propose that nongenetic mechanisms for reprogramming provide a novel and perhaps an essential strategy to accelerate application of regenerative medicine in the clinic. Keywords: dedifferentiation, transdifferentiation, reprogramming, pluripotency, microRNAs, epigenetic modifications, signaling pathways, toll-like receptors